2007
DOI: 10.1091/mbc.e06-08-0680
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Multiple Multivesicular Body Sorting Determinants within Sna3: A Role for the Ubiquitin Ligase Rsp5

Abstract: A subset of proteins that transit the endosomal system are directed into the intralumenal vesicles of multivesicular bodies (MVBs). MVB formation is critical for a variety of cellular functions including receptor down-regulation, viral budding, antigen presentation, and the generation of lysosome-related organelles. Entry of transmembrane proteins into the intralumenal vesicles of a MVB is a highly regulated process that is positively modulated by covalent modification of cargoes with ubiquitin. To identify ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
93
3
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(115 citation statements)
references
References 50 publications
18
93
3
1
Order By: Relevance
“…Sna3-GFP is degraded within the vacuole lumen subsequent to sorting into the MVB pathway; hence, its turnover serves as a measure of its MVB sorting (Oestreich et al, 2007). Consistent with microscopic analysis, loss of Mvb12 resulted in a decreased rate of turnover of Sna3-GFP ( Figure 3A and Supplemental Figure 2A).…”
Section: Identification Of Mvb12 As An Mvb Sorting Factorsupporting
confidence: 61%
See 2 more Smart Citations
“…Sna3-GFP is degraded within the vacuole lumen subsequent to sorting into the MVB pathway; hence, its turnover serves as a measure of its MVB sorting (Oestreich et al, 2007). Consistent with microscopic analysis, loss of Mvb12 resulted in a decreased rate of turnover of Sna3-GFP ( Figure 3A and Supplemental Figure 2A).…”
Section: Identification Of Mvb12 As An Mvb Sorting Factorsupporting
confidence: 61%
“…To more quantitatively address the intermediate phenotype observed in mvb12⌬ cells, kinetic analysis of Sna3-GFP sorting was performed by pulse-chase analysis ( Figure 3A and Supplemental Figure 2A). Sna3-GFP is degraded within the vacuole lumen subsequent to sorting into the MVB pathway; hence, its turnover serves as a measure of its MVB sorting (Oestreich et al, 2007). Consistent with microscopic analysis, loss of Mvb12 resulted in a decreased rate of turnover of Sna3-GFP ( Figure 3A and Supplemental Figure 2A).…”
Section: Identification Of Mvb12 As An Mvb Sorting Factorsupporting
confidence: 61%
See 1 more Smart Citation
“…Along these lines, recent studies show that Sna3 can utilize both ubiquitin-dependent and -independent mechanisms for its MVB targeting. Sna3 ubiquitination is dependent on Rsp5, but the function of Rsp5 is also critical for the MVB sorting of Sna3 independent of cargo ubiquitination (McNatt et al, 2007;Oestreich et al, 2007). Here we found that Ath1 has certain properties that are similar to Sna3.…”
Section: A New Signal For Protein Sorting Into Mvb Internal Vesiclesmentioning
confidence: 51%
“…Recent studies showed that Sna3 is also ubiquitinated; however, without ubiquitination it still can utilize an alternative mechanism, which involves the function of Rsp5, to be sorted into the MVB pathway (McNatt et al, 2007;Oestreich et al, 2007). Here we showed that the acid trehalase, Ath1, had the same transport behavior as Sna3.…”
Section: The Transmembrane Domain Of Ath1 Contains An Mvb Sorting Signalmentioning
confidence: 68%